2014
DOI: 10.1149/2.018405jes
|View full text |Cite
|
Sign up to set email alerts
|

Sarcosine Oxidase Encapsulated Polyvinyl Alcohol-Silica-AuNP Hybrid Films for Sarcosine Sensing Electrochemical Bioelectrode

Abstract: The amperometric response of sarcosine was measured in aqueous media containing ferrocene monocarboxylic acid using the redox enzyme sarcosine oxidase (SOD) immobilized in a composite material based on polyvinyl alcohol (PVA) and partially prehydrolyzed tetraethyl orthosilicate (pphTEOS) at the surface of-graphite electrodes. For comparison, separate electrodes consisting of silver and gold nanoparticles (Ag/AuNPs) embedded in the PVA-pphTEOS matrix was prepared employing a novel solgel process based on the in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(11 citation statements)
references
References 20 publications
1
8
0
Order By: Relevance
“…From the measurements, the following parameters can be extracted: for the GOx-coated part with glucose in solution K M = 6.9 ± 0.2 mM and for the SOx-coated part with sarcosine in solution K M = 7.2 ± 0.3 mM. Compared with the K M values determined for the enzymes in free solution (GOx: 26 mM, 50 SOx: 12.2 mM 51 ), they are smaller but in good agreement with apparent K M values reported for the immobilized GOx (2−31 mM) 10,52−54 and SOx (2−22 mM) 31,50,55,56 in sensor constructions.…”
Section: Multiplexed Detection Of Two Analytes In Parallel On a Chip ...supporting
confidence: 79%
“…From the measurements, the following parameters can be extracted: for the GOx-coated part with glucose in solution K M = 6.9 ± 0.2 mM and for the SOx-coated part with sarcosine in solution K M = 7.2 ± 0.3 mM. Compared with the K M values determined for the enzymes in free solution (GOx: 26 mM, 50 SOx: 12.2 mM 51 ), they are smaller but in good agreement with apparent K M values reported for the immobilized GOx (2−31 mM) 10,52−54 and SOx (2−22 mM) 31,50,55,56 in sensor constructions.…”
Section: Multiplexed Detection Of Two Analytes In Parallel On a Chip ...supporting
confidence: 79%
“…Sarcosine is known as a cancer biomarker for prostate cancer [71][72][73][74][75] and has been applied for early cancer detection through the electrochemical method. [76][77][78][79] The biomarker sarcosine was adopted for electrochemical detection by using the μEA sensor on the above-mentioned electrochemical detection platform.…”
Section: Reaction Chemistry and Engineering Papermentioning
confidence: 99%
“…Narwal et al [68] described the construction of an amperometric sarcosine biosensor based on covalent immobilization of SOX onto the nanocomposite of carboxylated multi-walled carbon nanotubes/CS and copper NPs (CS/CuNPs/MWCNT) modified gold electrode with better analytic performance. AuNPs have been also recently used for development of sensing system for sarcosine detection [69,70]. The size of prepared SPIONs (Figure 3) obtained by SEM analysis (18–28 nm) showed relatively narrow size distributions which are in accordance with the studies of Hirsch et al [71] that reported the size of 28.3 ± 2.1 nm in polyvinyl alcohol (PVA)-coated SPIONs (PVA-SPIONs), and of Park et al [72] that measured the size ranging from 22.4 to 25.1 nm in polymer-coated SPIONs.…”
Section: Discussionmentioning
confidence: 99%